(A) Development of Fe3O4/PS adsorbent for MB dye removal, (B) Methylene blue dye structure, and (C) Methyl Orange dye structure. - Tamer S. Saleh (5181146) (2025)
(A) Development of Fe3O4/PS adsorbent for MB dye removal, (B) Methylene blue dye structure, and (C) Methyl Orange dye structure.